Kajian budaya kontemporer - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Abstract The old-positivistic approach to cult are, which was insensitive to domination and inequality has heed seriously challenged by new approaches: post structural is and post-colonialist. This article maps out and elaborates r iau y ways of approaching culture in cultural studies.